2002
DOI: 10.2298/vsp0205479s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ribavirin efficacy and tolerance in subjects with chronic hepatitis C virus infection

Abstract: In this study ribavirin was more effective than placebo in reducing ALT levels during the treatment period of the applied therapy in patients with chronic active hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…Here we combine two single-dish datasets: one with much better resolution (Herschel) than the other (Planck). Therefore, we can make a loose analogy to previous interferometric techniques (e.g., Thompson et al 1986;Stanimirovic 2002) aimed at combining data sets that are observed at significantly different angular resolutions. Here Herschel would represent the interferometer data while Planck would represent the lower resolution single-dish data.…”
Section: Methods and Implementationmentioning
confidence: 99%
“…Here we combine two single-dish datasets: one with much better resolution (Herschel) than the other (Planck). Therefore, we can make a loose analogy to previous interferometric techniques (e.g., Thompson et al 1986;Stanimirovic 2002) aimed at combining data sets that are observed at significantly different angular resolutions. Here Herschel would represent the interferometer data while Planck would represent the lower resolution single-dish data.…”
Section: Methods and Implementationmentioning
confidence: 99%
“…The total interferometric flux of SMM1 at 1.3 mm is only 6.3% of the flux estimated from single-dish obervations whereas the interferometric flux for SMM2 is 12.5% expected from a single-dish measurement. This is probably due to the fact that structures larger than ≈1/4 of the primary beam size are filtered out by the interferometer (Stanimirovic 2002). With the larger 3 mm beam about 40 to 60% of the expected fluxes are recovered.…”
Section: High-resolution Mappingmentioning
confidence: 99%
“…Then, these large-scale data can be added to the interferometer data (Uyaniker et al 1998;Stanimirovic 2002). However, for the WSRT 350 MHz observations this is not possible.…”
Section: Wsrt Observations From 312-381 Mhzmentioning
confidence: 99%